2014
DOI: 10.1155/2014/456202
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Species Composition of Subaerial Algal Communities in Forested Areas of Meghalaya, India

Abstract: The study deals with a comparative study on diversity and species composition of subaerial algal communities from tree barks of closed undisturbed sacred grove, mixed plantation, and open disturbed forest. A total of 85 taxa had been recorded, 30 cyanobacteria and 55 algal species belonging to six classes of algae. Sacred grove harboured the highest subaerial algal diversity compared to those of plantation and open disturbed forest. There was a strong significant difference in species composition among the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Desmococcus sp., the most common green algae in the world [11] only presents at Station 3. Results from this study is in agreement with a study in Singapore where the result showed an insignificant result for Desmococcus sp [9]. Table 2 showed the indices for epiphytic terrestrial algae collected from the sampling stations.…”
Section: Species Percentage and Frequencysupporting
confidence: 91%
See 2 more Smart Citations
“…Desmococcus sp., the most common green algae in the world [11] only presents at Station 3. Results from this study is in agreement with a study in Singapore where the result showed an insignificant result for Desmococcus sp [9]. Table 2 showed the indices for epiphytic terrestrial algae collected from the sampling stations.…”
Section: Species Percentage and Frequencysupporting
confidence: 91%
“…Trebouxia sp. is usually found abundance on pollutant-rich stations [9]. Another species, Trentehpohlia sp.…”
Section: Species Percentage and Frequencymentioning
confidence: 97%
See 1 more Smart Citation
“…The level of diversity of Trentepohlia species in this study is similar to that in previous studies by Allali (2011) and Allali et al (2013) in Les Monts de Cristal National Park, Gabon, at an altitude of 100 to 800 m a.s.l., where 11 species were found. Kharkongor and Ramanujam (2014) studied areas of mixed plantation and open disturbed forest in Meghalaya, India, at an altitude of 958 to 1,710 m a.s.l., and found 11 species, and Neustupa and Škaloud (2008) studied the diversity of subaerial algae and cyanobacteria on tree bark in tropical mountain habitats in a Southeast Asian mountain rainforest in the Cibodas Biosphere Reserve, West Java, Indonesia.…”
Section: Diversity Of Algae and The Influence Of Environmental Factorsmentioning
confidence: 99%
“…A total number of 10 species had been reported [32], of which four species were dominant. Presence of high quantity of carotenoids was also documented from these four species of Trentepohlia [33].…”
Section: Introductionmentioning
confidence: 99%